Drought Induced Morphological and Biochemical Responses in Casuarina equisetifolia Clones - Warrier, Rekha R.; Bala Iyeswarya, M.; Marians Paul, M. (Indian Forester, 2016)
Casuarina equisetifolia Forst., a high economic value tree crop, supports land reclamation, dune stabilization and shelter belts also. Genetic improvement of the species has led to development of high yielding clones which need to be characterized for effective utilization of the resource in harsh sites. Cuttings of ten clones of Casuarina equisetifolia selected for productivity were grown under potted conditions and subjected to water stress through withdrawal. Comparative morphological and biochemical responses of the clones to drought conditions were studied. The levels of pigments and non-enzymatic antioxidants as well as the activities of antioxidant enzymes were quantified. Results showed significant differences in clones in their response to drought stress with respect to both fresh and dry weights of plants. Among biochemicals, chlorophyll a and b, enzymes catalase and peroxidase did not reveal any significant differences in response to drought. Real water contents in both roots and shoots varied under drought stress. There was an increase in both phenols and chlorophyll b contents under drought stress. Furthermore, proline activity reduced in drought treated plants. This was observed in all the clones. It is therefore, obvious that all of these characters play essential roles in the drought tolerance of plants. Clones also exhibited significant differences in their ability to respond to drought stress. Activities of chlorophyll a, peroxidase and a:b ratio were the only parameters which did not differ significantly between clones suggesting their activities to be stable in the species. These results indicate that phenols, chlorophyll activity and proline levels in different tissues could be used as markers of drought tolerance in casuarinas clones. Further, this study emphasized the role of sugars involved in ROS detoxification during drought stress, and identified potential clones for deployment in difficult sites.